Six-wave interaction in multimode waveguides with Kerr nonlinearity with allowance for the Gaussian structure of pump waves - V.V. Ivakhnik; D.R. Kapizov; V.I. Nikonov (Компьютерная оптика)
The quality of wavefront conjugation in the case of six-wave interaction in two-dimensional multimode waveguides with Kerr nonlinearity is analyzed under the condition that one of the pump waves excites a zero waveguide mode and the amplitude distribution of the other pump wave at the waveguide end facet varies according to the Gauss law. It is shown that in a waveguide with infinitely conducting walls, the half-width of the modulus of the point spread function of a six-wave radiation converter is completely determined by the transverse size of the waveguide and weakly depends on the width of the Gaussian pump wave. In a parabolic-index profile waveguide, a decrease in the width of the Gaussian pump wave at the waveguide ends commonly leads to a monotonic decrease in the half-width of the point spread function modulus.